The tranformative perspective in critical reflection and dialogue among former drug addict in petaling jaya, Selangor, Malaysia - Abu Hassan, Normala; Azhar Abd Hamid, Mohd; Hassan, Zainudin; Tukiman, Kassim; Koharudin, Mohd (International Journal of Engineering and Technology, 2018)
The purpose of this study is to discuss the function of critical reflection and dialogue through perspective transformation process among 15 former drug addict. This paper will discusses the learning process of the former drug addicts return to normal life. One of the learning elements that applies in the adult cognitive system (in this context is the former addict drug) is a critical reflection. Critical reflection is an important element in transformative learning which former drug addict trying to find a solution to drug addiction by doing critical reflection to their past experience. They will reflect, think again, check and examine the experience as a drug addict. In addition, the dialog element is important in critical reflection which can respond to experience of former drug addicts. Dialogue is a process by which the former drug addict dialogue with other individuals to build a new perspective and is a process is important element in transformative learning. Critical reflection and dialogue an effective learning process for adults. The main theory of this study is transformative learning theory by Mezirow. Qualitative methods was chosen in this study by using the phenomenological and case study method in which to understand the phenomenon comprehensively. Finally, this article will conclude the critical reflection and dialogue function to help former drug addicts.Â Â